Extended balance stabilization control for humanoid robot on rotational slope based on seesaw-inverted-pendulum model. (17th September 2021) - Kimura, Kohei; Okada, Kei; Inaba, Masayuki
Abstract : This paper proposes an extended balance stabilization control approach for humanoid robot on rotational slope. We define rotational slope as the unstable rotated slope where humanoid robot rides. Conventional balance stabilization control enables humanoid robot to stand stably on the flat floor and the uneven ground. Although the balance stability for only humanoid robot can be guaranteed by the conventional approach, rotational slope cannot be stabilized successfully. In this paper, we propose seesaw-inverted-pendulum model to stabilize the balance of both humanoid robot and rotational slope. Seesaw-inverted-pendulum model is the generalized control model that humanoid robot is regarded as inverted pendulum composed of center of mass and zero moment point of robot and rotational slope is regarded as seesaw dynamics. We apply the extended balance stabilization control based on seesaw-inverted-pendulum model to a real life-sized humanoid robot and verify the balance stabilization results on the wobble floor and the unicycle Segway by experiments. GRAPHICAL ABSTRACT: UF0001